Neurological manifestations associated with COVID-19 in Edgardo Rebagliati Martins Hospital, Peru - Mariños Sánchez, Evelyn (2021)
The disease caused by coronavirus 2 associated with severe acute respiratory syndrome (SARS-CoV-2) is formally known as Coronavirus Disease 2019 (COVID-19). Its main focus is the respiratory system, but neurological manifestations have also been described. Objective: To describe the neurological manifestations in patients with COVID-19 at the Edgardo Rebagliati Martins hospital. Material and Methods: An observational, descriptive, cross- sectional study, using the electronic medical records of COVID-19 hospitalized and discharged during the April- August 2020 period. The patients were classified as carrying neurological manifestations of the central and peripheral nervous system. Results: Of 1122 patients, 354 (31.5%) had some neurological manifestation while 26.9% showed symptoms of the central nervous system (CNS), and 8.4% of the peripheral nervous system (PNS). Among the CNS manifestations, the most frequent symptom was headache (19.7%), and as pathologies: encephalopathy (4.7%), ischemic stroke (2.7%), acute symptomatic seizure (0.5%), cerebral hemorrhage (0,4%), encephalitis (0.2%). From the PNS manifestations, myalgia (3.4%), anosmia (3.1%) and dysgeusia (2.9%) predominated and, as pathologies, rhabdomyolysis (1.3%) and acute polyradiculoneuropathy (0.3%). The fatality rate reached 32.7% with an OR of 1.4. Conclusions: Patients with SARS-CoV-2 infection can present neurological symptoms as those described in the present study, manifestations that should be considered in their timely and integrated care.